A revision of the Afrotropical species of Pachylophus Loew (Diptera: Chloropidae) and some related Ovoviviparous genera - Deeming, John C. (Zootaxa, 2018)
In Pachylophus all described Afrotropical species are treated and P. aristalis, ismayi, nigeriensis, tschirnhausi, mirabilis, lacteibasis and stuckenbergi are described as new species. Pachylophus tellinii Bezzi is placed in synonymy. In Phyladelphus the type species thalhammeri and the single described Afrotropical species, P. geminus, are treated and P. woodi and P. maraisi are described as new species. The genus Sabeurina is erected to accommodate Eurina minuta Loew and a new Afrotropical species S. occidentalis. Some taxonomic notes are given on the Afrotropical species currently included in Platycephala. The immature stages and biological notes concerning the treated genera are described and discussed in the contexts of ovoviviparity and classification. Keys are provided for the identification of all the Afrotropical species known in each of the genera treated.